A Novel Nonsense Mutation in FERMT3 Causes LAD-III in a Pakistani Family - Shahid, Saba; Zaidi, Samreen; Ahmed, Shariq; Siddiqui, Saima; Abid, Aiysha; Malik, Shabbir; Shamsi, Tahir (Frontiers in Genetics, 2019)
Leukocyte Adhesion Deficiency (LAD) type 3 is very rare primary immunodeficiency. This is caused by genetic alteration in the FERMT3 gene, which leads to abnormal expression of kindlin-3 protein. This protein is highly expressed on leukocytes and platelets membranes and acts as an important player to regulate integrin activation. It has features like bleeding syndrome of Glanzmann-type and leukocyte adhesion deficiency. The mutation of FERMT3 gene in patients with LAD-3 in an autosomal recessive pattern has not been well characterized in Pakistani population. In this study, an infant and his family of Pakistani origin with clinical features of LAD were investigated for the underlying genetic defect. Targeted next generation sequencing (TGS) as well as Sanger sequencing were performed to confirm causative mutations and their segregation in the family. A novel, homozygous nonsense variant (c.286C>T, p.Q96*) in the FERMT3 gene was found in the proband with autosomal recessive pattern LAD-3 and their co-segregation was confirmed with the clinical phenotypes. Both parents were carriers of the same mutation. This family was offered prenatal diagnosis in subsequent pregnancy during first trimester; fetus carried the trait. In closure, our study is the first report to identify the novel homozygous variant c.286C>T, p.Q96* in the FERMT3 gene which might be the causative mutation for LAD-3 patient of Pakistani origin.